Quantitation of Methanol & Acetaldehyde from Raw & Black Garlic by Headspace GC with PLOT Column - Oh, Chang-Hwan (International Journal of Engineering and Technology, 2018)
Background/Objectives: Black garlic is produced by heating a garlic at 60 70Â°C for a couple of weeks. Methanol and acetaldehyde are toxic chemicals that could be produced naturally from plant materials.Methods/Statistical analysis: Methanol and acetaldehyde contents in the raw and black garlic were measured. Manual static headspace (HS) sampling method was established and GC analysis with PLOT column was applied. Black garlic was prepared in a rice cooker at 60 70Â°C for three weeks followed by drying for two weeks. The ratio of water and mashed garlic for the preparation of the garlic extract was optimized.Findings: The optimum ratio between the garlic sample and water was 1:2 for the preparation of headspace liquid sample. The HS sample in the 20mL vial (containing 3 mL of garlic extract) was analyzed. Acetaldehyde detected as large amount comparing to methanol was almost gone in black garlic. It might be too volatile to survive in that harsh condition such as heating at 60 70Â°C for a couple of weeks. The analyzed methanol content in the black garlic was about 6 times higher than the raw garlic. That means the methanol derived from the pectin might be increased even at the relatively mild heating condition. If two weeks of the drying period was considered, actual amount of methanol occurred during the heating process might be higher than that. The naturally occurring methanol from the plant materials containing pectin is very popular in our dish. Moreover, the heating process is the essential part of cooking. Hazardous chemicals such as methanol are more likely to be present during common cooking processes.Improvements/Applications: The manual headspace sampling is very simple and easy to apply even without the expensive instruments specifically dedicated for the automatic headspace sampling. Moreover, the PLOT column is also a very efficient tool even without the concentration trap to decrease the peak width. The method could be applied in any laboratory if they have a GC-FID.Â Â